Heavy Menstrual Bleeding in the Adolescent Patient - Francis, Jessica C. (Current Women's Health Reviews, 2018)
Background: Both the American Academy of Pediatrics and American College of Obstetricians and Gynecologist endorsed the use of the menstrual cycle as a vital sign, emphasizing the importance of talking to females about their periods. Irregular menses is one of the most common complaint of adolescents presenting to the gynecologist and may be the symptom of a more serious diagnosis. Heavy menstrual bleeding (HMB) is common among adolescents with up to 37% reporting heavy bleeding. The workup that is done should be tailored to the individual patient. There are several treatment options based on the etiology of HMB. Recent Findings: The appropriate workup for adolescents who complain of heavy menstrual bleeding continues to be evaluated and re-defined. Underlying bleeding disorders need to be considered in these patients. Federal programs have made proper evaluation and referral an objective for Healthy People 2020. A number of non-surgical therapeutic options exist. Tranexamic acid and the levonorgestrel intrauterine device have had very favorable outcomes for treatment of HMB. Conclusion: Heavy menstrual bleeding is common among adolescents and may be a sign of a more significant underlying medical problem so proper evaluation is imperative. Regardless of the etiology, effective treatment can drastically improve symptoms.
Keywords: birth control